(untitled) - Budgell, Gill (Cambridge, 2015)
Cambridge Primary English is a flexible, endorsed course written specifically to support Cambridge International Examinations' curriculum framework (Stages 1-6). Phonics is a vital skill to master for young learners who must match the written letters with the spoken sounds in English and use this knowledge to read and spell. Cambridge Phonics Workbook A is aimed at learners aged between 4 and 5 and is a foundation stage in phonics skills, while Phonics Workbook B is intended for use in Year 1 (ages 6 to 7), and can be used alongside Stage 1 of the Cambridge Primary English course or with similar courses. The books are appropriate for children who have English as a first or as a second language.
Keywords: English language,Tiếng Anh; Phonetics,Ngữ âm học